Объяснение:
1) Al2O3 + 6HNO3 =2 Al(NO3)3 + 3H2O (1+6+2+3=12)
3Ba + 2H3PO4 = Ba3(PO4)2 +3 H2 (3+2+1+3=9)
CuO + 2HNO3 = Cu(NO3)2 + H2O (1+2+1+1=5)
Fe(OH)3 + 3HCl = FeCl3 + 3H2O (1+3+1+3=8)
3Na2O + 2H3PO4 = 2Na3PO4 +3 H2O (3+2+2+3=10)
BaO + H2S = BaS + H2O (1+1+1+1=4)
2LiOH + H2SO4 = Li2SO4 + 2H2O (2+1+1+2= 6)
Ca(OH)2 + 2HBr = CaBr2 + 2H2O (1+2+1+2=6)
2) Mg + H2SO4 = MgSO4 + H2
2Na + 2HCl = 2NaCl + H2
3Ca + 2H3PO4 = Ca3(PO4)2 +3H2
Hg + HBr = реакция не идёт
Cu + HCl = реакция не идёт
2Al + 6HBr = 2AlBr3 + 3H2
Объяснение:
1) Al2O3 + 6HNO3 =2 Al(NO3)3 + 3H2O (1+6+2+3=12)
3Ba + 2H3PO4 = Ba3(PO4)2 +3 H2 (3+2+1+3=9)
CuO + 2HNO3 = Cu(NO3)2 + H2O (1+2+1+1=5)
Fe(OH)3 + 3HCl = FeCl3 + 3H2O (1+3+1+3=8)
3Na2O + 2H3PO4 = 2Na3PO4 +3 H2O (3+2+2+3=10)
BaO + H2S = BaS + H2O (1+1+1+1=4)
2LiOH + H2SO4 = Li2SO4 + 2H2O (2+1+1+2= 6)
Ca(OH)2 + 2HBr = CaBr2 + 2H2O (1+2+1+2=6)
2) Mg + H2SO4 = MgSO4 + H2
2Na + 2HCl = 2NaCl + H2
3Ca + 2H3PO4 = Ca3(PO4)2 +3H2
Hg + HBr = реакция не идёт
Cu + HCl = реакция не идёт
2Al + 6HBr = 2AlBr3 + 3H2
1)а)koh+ba(no3)2=k(no3)2+ba(oh)2
б)niso4+(nh4)2s=nis+(nh4)2so4
в)pb(no3)2+2kcl=pbclw-2kno3
г)cucl2+na2s->cus+2nacl
cu(2+)+2cl(-)+2na(+)+s(2-)->cus+2na(+)+2cl(-)
cu(2+)+s(2-)->cus
2)а)ch3coona+hcl=ch3cooh+nacl
ch3coo(+)+cl(-)+ch3cooh
ch3coo(-)+h(+)=ch3cooh
б)bacl2+na2cro4=bacro4+2nacl
ba(+2)+2cl(-)+2na(+)+cro4(2-)=bacro4+2na(+)+2cl(-)